Interdependence of death and the plot. - Phoong, Kai Wen. (2011)
Death has intrigued and even inspired fear in many. Since fiction mimics life, it is no wonder that Death has been a recurrent theme in literature for centuries either. Literatures of the 15th century are no strangers to the theme of death either. However, it was not until recently that death anxiety studies are researched as a science, in the form of thanatology. How then, does this change our view towards the means that literature interacts with the real world? Does this change the way we view literatures? It can be argued that literature offers to the living a repose from life, and is exploratory in nature of the unknown. As an entity of unknown, again, the multifarious ways that death manifests itself in literatures are justified. Not only so, should the plot induce death, or is it that death inspires the necessity of a plot. Studying modern works of literatures, this paper aims to find out the relationship between death and the plot, and how they support, or disavow some theories of thanatology. This paper examines how death shapes the author, narrator and character as well as how decisions and choices affect each other. It then goes on to suggest an identity for death in modern fiction and looks into the issue of self-destruction. Finally this paper explores the universality of death, not only in life, but in fiction, and tries to find if that affects the way we live our lives.